Role of the Banking System in Promoting Sustainable Solutions For the Egyptian Agricultural Sector: A Field Study - Al-Deq, Waleed Mahmoud Mohamad Ahmed (The Arab Journal of Administration, 2024)
The current study aimed to analyze the role of the banking system in promoting sustainable solutions for the Egyptian agricultural sector, through a questionnaire list that was distributed to a sample of employees of the Agricultural Bank of Egypt and faculty members and their assistants in Egyptian universities. The number of questionnaires distributed reached 105 items, and the hypotheses were tested using analysis Simple regression. The study relied on the descriptive analytical approach as a method of study, which relies on two methods: desk study and field study. Through the field study, the researcher reached many results, the most important of which are: The members of the study sample have sufficient awareness and understanding of the role of the banking system in facing challenges and promoting sustainable solutions for the Egyptian agricultural sector، and Accepting the first hypothesis of the study, which states that: There is a statistically significant relationship between the banking system and facing the challenges facing the Egyptian agricultural sector from the point of view of the study sample members, and accepting the second hypothesis of the study, which states that: There is a statistically significant relationship between the banking system and promoting sustainable solutions for the Egyptian agricultural sector from the point of view of the study sample members, Based on the results of the study, a number of recommendations were presented, including the necessity of the banking sector should make more efforts and supportive steps to support the goals of sustainable development by establishing a department specialized in sustainable banking financing within its organizational structure (the General Administration of Sustainable Finance), and to then be the starting point towards Establishing a bank specialized in sustainability directed to provide its services to all economic sectors. Prospects for future studies were also presented.